A Sensitive Bioimmunoassay for Thrombin-cleaved Two-chain Urokinase-type Plasminogen Activator in Human Body Fluids - Braat, Ellen A M; Nauland, Ume; Dooijewaard, Gerard; Rijken, Dingeman C (Thrombosis and Haemostasis, 1996)
Thrombin cleaves single-chain urokinase-type plasminogen activator (scu-PA) into a two-chain form (tcu-PA/T), which is virtually inactive in plasminogen activator assays. Little is known about the physiological importance of tcu-PA/T. To examine the occurrence of tcu-PA/T in vivo, we developed a sensitive and specific bioimmunoassay (BIA) for the assessment of tcu-PA/T in human body fluids. In this BIA, urokinase antigen was immuno-immobilized in microtiter plates and treated with cathepsin C, a specific activator of tcu-PA/T, after which plasminogen activator activity was measured. The occurrence of tcu-PA/T was examined in the plasma of 27 healthy individuals and of 17 sepsis patients, and in the synovial fluid of 16 rheumatoid arthritis patients. In addition, the concentration of urokinase antigen and scu-PA were measured in all three groups. In the plasma of the healthy individuals no measurable amounts of tcu-PA/T could be found (< detection limit of 0.2 ng/ml). In the plasma of almost all sepsis patients tcu-PA/T could be detected (median value 0.4 ng/ml). The amount of tcu-PA/T was 12% of the amount of scu-PA and accounted for about 9% of urokinase antigen. In the synovial fluid of all rheumatoid arthritis patients tcu-PA/T could be measured (median value 5.4 ng/ml) at a concentration which was twofold higher than the concentration found for scu-PA. In this group tcu-PA/T contributed to about 47% of the urokinase antigen. From these data we conclude that inactivation of scu-PA by thrombin can take place in vivo under pathological conditions which involve the production of large amounts of thrombin. This way thrombin may regulate fibrinolysis and extracellular proteolysis. The BIA for tcu-PA/T can be of use for further research on the physiological role of tcu-PA/T.